Mapping the Types and Function of Code Mixing Utilized by Boy William in His YouTube - Ekalia, Yulian; Fransiskus Jemadi; Leonardus Par (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to examine the types and functions of code mixing used by Boy William in his YouTube videos. A descriptive qualitative approach was employed to analyse the linguistic data collected from four selected videos on his channel. The findings revealed that four types of code mixing were present in Boy William’s speech: unit insertion, unit hybridization, sentence insertion, and reduplication. A total of 23 instances of code mixing were identified across the selected videos, with the following distribution: 10 cases of unit insertion, 4 of unit hybridization, 8 of sentence insertion, and 1 of reduplication. Additionally, seven functions of code mixing were identified, including expressing emotion, asserting status, showing pride, enhancing clarity, making jokes, fulfilling communicative needs, and reflecting prestige. Based on this research, it can be concluded that code mixing is a common feature in Boy William’s YouTube content, serving various social and communicative purposes. The findings of this study offer an implication, particularly in the fields of sociolinguistics in which in sociolinguistics perspective, this research contributes to a deeper understanding of how multilingual speakers use code mixing as a communicative strategy in informal digital platforms like YouTube.